Introduction to international and global studies - Smallman, Shawn C.; Brown, Kimberley, 1966- (The University of North Carolina Press, 2020)
"This innovative introduction to international and global studies, updated and revised in a new edition, offers instructors in the social sciences and humanities a core textbook for teaching undergraduates in this rapidly growing field. Encompassing the latest scholarship in what is a markedly interdisciplinary endeavor, Shawn Smallman and Kimberley Brown introduce key concepts, themes, and issues and then examine each in lively chapters on essential topics that include the history of globalization; economic, political, and cultural globalization; security, energy, and development; health; agriculture and food; and the environment. Within these topics, the authors explore such timely and pressing subjects as commodity chains, labor (including present-day slavery), human rights, multinational corporations, and the connections among them"--